Odpowiedzi

2010-04-06T18:51:25+02:00
E) 3(x+3)= 2(x+4)+x+1
3x+9 = 2x+8+x+1
3x-2x-x = 1+8-9
0=0

f) 4(3x+2)+5(2x+3)= -(2x+13)
12x+8+10x+15 = -2x-13
12x+10x+2x = -13-8-15
24x = -36 / : 24
x = - ³⁶/₂₄
x= - 1 ¹²/₂₄
x = - 1 ½

g) 4 (x-2) -2 (x-4)= 5(x+1)-3x
4x-8-2x+8 = 5x+5-3x
4x-2x-5x+3x = 5+8-8
0=5 fałsz

h) 2(x-4)= 2(2x-1)+6(x+1)
2x-8 = 4x-2+6x+6
2x-4x-6x = -2+6+8
-8x = 12 / : (-8)
x = - ¹²/₈
x = - 1 ⁴/₈
x = - 1 ½
1 5 1
2010-04-06T18:54:24+02:00
E) 3(x+3)= 2(x+4)+x+1
3x+9=2x+8+x+1
3x+9=3x+9
0=0 prawda


e)
3(x+3)= 2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x-x=8+1-9
0=0

f)
4(3x+2)+5(2x+3)= -(2x+13)
12x+8+10x+15=-2x-13
12x+10x+2x=-13-8-15
24x=-36
x=-1,5

g)
4 (x-2) -2 (x-4)= 5(x+1)-3x
4x-8-2x+8=5x+5-3x
4x-2x-5x+3x=5+8-8
0≠5

h)
2(x-4)= 2(2x-1)+6(x+1)
2x-8=4x-2+6x+6
2x-4x-6x=-2+6+8
-8x=12
x=-1,5
na pewno dobrze;)liczę na naj
1 5 1
2010-04-06T19:47:59+02:00
E)
3(x+3)= 2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x-x=8+1-9
0=0

f)
4(3x+2)+5(2x+3)= -(2x+13)
12x+8+10x+15=-2x-13
12x+10x+2x=-13-8-15
24x=-36
x=-1,5

g)
4 (x-2) -2 (x-4)= 5(x+1)-3x
4x-8-2x+8=5x+5-3x
4x-2x-5x+3x=5+8-8
0≠5

h)
2(x-4)= 2(2x-1)+6(x+1)
2x-8=4x-2+6x+6
2x-4x-6x=-2+6+8
-8x=12
x=-1,5